2010
DOI: 10.1371/journal.pone.0008857
|View full text |Cite
|
Sign up to set email alerts
|

Two Very Long Chain Fatty Acid Acyl-CoA Synthetase Genes, acs-20 and acs-22, Have Roles in the Cuticle Surface Barrier in Caenorhabditis elegans

Abstract: In multicellular organisms, the surface barrier is essential for maintaining the internal environment. In mammals, the barrier is the stratum corneum. Fatty acid transport protein 4 (FATP4) is a key factor involved in forming the stratum corneum barrier. Mice lacking Fatp4 display early neonatal lethality with features such as tight, thick, and shiny skin, and a defective skin barrier. These symptoms are strikingly similar to those of a human skin disease called restrictive dermopathy. FATP4 is a member of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 38 publications
2
78
1
Order By: Relevance
“…The C. elegans genome contains 22 genes known to encode acyl-CoA synthetase/fatty acid transporter (Zhang et al 2013), of which ACS-20 is required for incorporation of exogenous very long chain fatty acids into sphingomyelin (Kage-Nakadai et al 2010). While ACS-22 may functionally overlap with ACS-20 (Kage-Nakadai et al 2010), we found that only ACS-20 is required for the increased fat accumulation under iron overload, suggesting that ACS-20, like SGK-1, regulates lipid hemostasis under iron overload.…”
Section: Discussionmentioning
confidence: 99%
“…The C. elegans genome contains 22 genes known to encode acyl-CoA synthetase/fatty acid transporter (Zhang et al 2013), of which ACS-20 is required for incorporation of exogenous very long chain fatty acids into sphingomyelin (Kage-Nakadai et al 2010). While ACS-22 may functionally overlap with ACS-20 (Kage-Nakadai et al 2010), we found that only ACS-20 is required for the increased fat accumulation under iron overload, suggesting that ACS-20, like SGK-1, regulates lipid hemostasis under iron overload.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest are the acyl-CoA synthetase (ACS) family, the homologue of mammalian adipose triglyceride lipase ATGL-1, and the short chain fatty acid dehydrogenases (DHS) family. C. elegans ACS-20 and ACS-22 are implicated in the incorporation of very long chain fatty acids into sphingomyelin, which may be linked to cuticle barrier formation (30). DHS-28, a peroxisomal dehydrogenase, has been shown to regulate long chain fatty acid ␤-oxidation and LD size (21).…”
Section: Discussionmentioning
confidence: 99%
“…S3). Furthermore, Kage-Nakadai (25) reported that very long chain fatty acyl-CoA synthetase plays an important role in the cuticle surface barrier. As both POD-2 and FASN-1 contribute to the biosynthesis of MUFA and polyunsaturated fatty acids in C. elegans (26), it would be reasonable to predict that RNAi against pod-2 and fasn-1 would affect cuticle integrity.…”
Section: Discussionmentioning
confidence: 99%